Rescue of synthetic genomic RNA analogs of rabies virus by plasmid-encoded proteins. - Conzelmann, K K (1994)
Proteins entirely expressed from cDNA were used to rescue synthetic RNA genome analogs into infectious defective particles of rabies virus (RV). Synthetic negative-stranded RNAs containing 3'- and 5'-terminal RV sequences and transcriptional signal sequences were transcribed from plasmids transfected into cells expressing T7 RNA polymerase from recombinant vaccinia virus. After simultaneous expression of RV N, P, and L proteins from plasmids containing a T7 RNA polymerase promoter, the synthetic genomes were encapsidated, replicated, and transcribed by the RV polymerase proteins. Insertion of the bacterial chloramphenicol acetyltransferase gene or beta-galactosidase (lacZ) gene between the 3' and 5' termini containing transcriptional signal sequences resulted in transcription of mRNAs and expression of chloramphenicol acetyltransferase and beta-galactosidase, respectively. Upon simultaneous expression of N, P, M, G, and L proteins, virions carrying the foreign genes were assembled and released into the supernatant. The possibility of rescuing cDNA into rabies virions by proteins also expressed entirely from cDNA opens the possibility of studying the functions of each RV protein and analyzing cis-acting signals of the RV genome.